Democracy and Sovereignty in Spain Conceptual Innovation in the Spanish Constituent Assembly of 1931 - Bellido, Francisco J. (Routledge/Canada Blanch Studies on Contemporary Spain, 2023)
This book delves into the conceptual changes produced by the Spanish constitutional debate held between 27 August and 9 December 1931. Taking place at the beginning of Spain's Second Republic, those parliamentary deliberations brought about significant novelties in the political vocabulary. Concepts such as democracy, sovereignty, reform, revolution, and freedom, among others, were re-signified. This study investigates the conceptual contributions made by Spanish MPs in the course of the constitutional debate of 1931 by assuming, as a research approach, an interdisciplinary stance combining conceptual history, political theory, and parliamentary constitutional history. By doing so, it selects five determining issues: the pervasive discussion about two competing meanings of a democratic state; the rhetorical uses of reform and revolution; conceptual controversies about religious freedom; the disputed idea of property rights; and the functions of parliament and the president of the republic in a semi-presidential regime. The constitutional debate was largely inspired by interwar European constitutionalism which constituent representatives used to update the Spanish constitutional tradition. With that goal in mind, this book is aimed at undergraduate and graduate students and scholars working in the fields of conceptual history, political philosophy, parliamentary history, European political history, and European constitutionalism.